Analisis Kepatuhan Dokter Dalam Mengisi Rekam Medis Di Rumah Sakit Umum Daerah Kabupaten Boyolali - , Istirochah; , Drs. M. Farid Wajdi, MM., Ph.D; , DR.Syamsudin, M.M (2017)
This study aims to determine the completeness of the filling of medical records by doctors at hospitals Boyolali, and analyze the factors that influence compliance doctors in charge of medical records in hospitals Boyolali. The study population was all doctors at Boyolali hospitals. The sample selection criteria using purposive sampling with an authorized doctor and involved in health care in hospitals Boyolali. The data used are primary data was collected using a questionnaire. Analysis of data using multiple linear regression. The conclusions of this research are (1) compliance the doctor in charge of medical records is very high. More than 50% of respondents have high scores on. (2) doctor compliance in charge of medical records in Boyolali hospitals influenced by the four independent variables simultaneously, and (3) in partial doctors compliance in charge of medical records in hospitals Boyolali been affected by incentives and doctor perception on SOP and Form fields of medical records